2017
DOI: 10.1001/jamaophthalmol.2017.0089
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Screening Patterns Among Youths With Diabetes Enrolled in a Large US Managed Care Network

Abstract: IMPORTANCE Ophthalmic screening to check for diabetic retinopathy (DR) is important to prevent vision loss in persons with diabetes. The American Academy of Ophthalmology recommends that ophthalmic screening for DR occur beginning at 5 years after initial diabetes diagnosis for youths with type 1 diabetes; the American Diabetes Association recommends screening of youths with type 2 diabetes at the time of initial diagnosis. To our knowledge, it is unknown to what extent youths with diabetes obtain eye examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 36 publications
(89 reference statements)
6
51
0
Order By: Relevance
“…The moderate effect size observed is consistent with those found elsewhere in behavioural medicine (26) The low overall sample size combined with a high baseline screening rate (72%) resulted in a lack of power to detect change in the primary outcome. Although similar to the general diabetes population screening rate in Australia (78%, 11) national and international data suggest that the true younger adult screening rate is closer to 50% (9,10), indicating that the current study is likely to have experienced recruitment bias. Possible explanations for recruitment bias, which favors high selfreported screening rates, include: self-selection bias and social desirability and recall bias (34).…”
Section: Summary Of Findingssupporting
confidence: 52%
See 1 more Smart Citation
“…The moderate effect size observed is consistent with those found elsewhere in behavioural medicine (26) The low overall sample size combined with a high baseline screening rate (72%) resulted in a lack of power to detect change in the primary outcome. Although similar to the general diabetes population screening rate in Australia (78%, 11) national and international data suggest that the true younger adult screening rate is closer to 50% (9,10), indicating that the current study is likely to have experienced recruitment bias. Possible explanations for recruitment bias, which favors high selfreported screening rates, include: self-selection bias and social desirability and recall bias (34).…”
Section: Summary Of Findingssupporting
confidence: 52%
“…Guidelines recommend screening for DR at T2D diagnosis, repeated periodically thereafter (5)(6)(7). Despite this, young adults with T2D have lower screening uptake in comparison with other groups (8,9). In Australia, screening rates in this priority population are estimated to be 55%, compared with 78% in the general diabetes population (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Severe retinopathy or macular oedema was present in 2% and the youngest patient with PDR was age 6 years. Lower rates of screening uptake were found in those with lower family income and this group had higher rates of retinopathy, suggesting that the actual rate may be even higher …”
Section: Introductionmentioning
confidence: 93%
“…84,85 In the T1D Exchange Registry in the United States, less than 1% of 12 235 patients reported treatment for retinopathy 86 were found in those with lower family income and this group had higher rates of retinopathy, suggesting that the actual rate may be even higher. 87,88 Initial worsening of diabetic retinopathy can occur with the initiation of improvement in glycemic control as occurred in the DCCT but such worsening did not result in clinically significant visual loss and over time, intensive therapy continued to be superior to standard therapy. This initial worsening of diabetic retinopathy with improvement of glycemic control also occurred in patients with growth failure due to severe under-insulinization.…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…The National Pediatric Diabetes Audit (NPDA), which uses data reported routinely by pediatricians caring for children living with diabetes, reported that only 66% of the UK's eligible children were reported to have undergone screening in 2015/2016, with uptake ranging from 0% to 100% by unit (median: 74%; IQR: 65‐81%) . Similar low screening attendance has been reported in the US where 66% of children and young people (CYP) living with type 1 and 42% of those living type 2 diabetes had undergone retinal examination by 6 years following diagnosis . Uptake of DR screening decreases during adolescence, especially during transition to adult services, a period when non‐adherence to glycaemia control measures.…”
Section: Introductionmentioning
confidence: 53%